Perception on land owners toward oil palm land development scheme: a case study in Samarahan division - Phang, Joon Foong (Universiti Malaysia Sarawak (UNIMAS), 2005)
(RIa pid economic growth experienced since independence has brought about socialeconomy disparities between rural and urban society in this country. Consequently the challenge of expediting alleviation of poverty particularly among the rural community is a national priority. In this connection, Sarawak state government has formulated an appropriate development concept termed as "in-situ land scheme concept" which is extensively adopted in the rural land development programme through various land development agencies. Since then, the initiative in targeting NCR land for monoculture plantation (Oil Palm) washsýe en as capable of reducing social-economic imbalance between rural and urban environmentýi. However, the geographical terrain, logistical access, social sentiment are amongst local problems that may scare away potential developers from the capital intensive endeavour. Conflicts of interest between developers and landowners of often jeopardize the entire objective of development brought by the government. This study, therefore, attempts to assess the perceptions of land scheme participants after a given period of participation in the scheme. Two areas developed by different agencies involving two different communities were chosen as scope of study area. The specific objectives are to determine the direct benefits enjoyed by the participants of the two areas, and to examine if the perception of participant has influenced the state of attitude that caused impact to their own household economy.